2022
DOI: 10.1002/smll.202107437
|View full text |Cite
|
Sign up to set email alerts
|

Molten Salt Shielded Synthesis of Monodisperse Layered CaZnOS‐Based Semiconductors for Piezophotonic and X‐Ray Detection Applications

Abstract: light-generators, stress sensing, flexible, and stretchable displays, mechanical energy harvesting and conversion, and integrated tribotronic devices. [1][2][3][4][5][6][7][8][9][10] They can emit light and are regarded as smart creatures (like Noctiluca scintillans shining by the impact of waves) when exposed to external momentary stimuli. [11][12][13][14] Many materials discovered in nature provide the capability to emit light in response to dynamic forces/pressures, whether natural or man-made, such as quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The presence of liquid-phase molten salts between the generated powders prevents the particles from contacting and linking with each other. [41][42][43] What's more, most conventional syntheses with molten salts require washing away them at the end, which could have an impact on the surface properties of the products and adds to complication of the experiment. [44][45][46] In this case, NaCl evaporates away gradually at high temperatures after coming into play.…”
Section: Mechanism and Advantagesmentioning
confidence: 99%
“…The presence of liquid-phase molten salts between the generated powders prevents the particles from contacting and linking with each other. [41][42][43] What's more, most conventional syntheses with molten salts require washing away them at the end, which could have an impact on the surface properties of the products and adds to complication of the experiment. [44][45][46] In this case, NaCl evaporates away gradually at high temperatures after coming into play.…”
Section: Mechanism and Advantagesmentioning
confidence: 99%
“…ML refers to the phenomenon where materials emit light under mechanical stimulation (friction, stretching, compression, tearing, etc. ), which is regarded as an effective way to realize mechanical distribution detection and imaging and has received extensive attention in earlier research work. For example, in 2008, Li et al coated a SrAl 2 O 4 : Eu 2+ composite film on a hole-drilled aluminum plate, and the intensity of the ML of the SrAl 2 O 4 : Eu 2+ film during the application of tensile forces to the surface of the plate was recorded using a high-speed CCD camera; it was finally found that the finite element method stress distribution calculation was the same as the strength distribution detected by ML. In 2012, Terasaki et al recorded a SrAl 2 O 4 : Eu 2+ composite film embedded in the gap of a concrete bridge, and the local ML image in the process of vehicles passing through the bridge was recorded by a sensitive CCD camera.…”
Section: Introductionmentioning
confidence: 99%
“…[95] The molten salt method is very convenient and low-cost and may be advantageous in terms of luminescent brightness. For some other oxidation-prone ML compounds [96][97][98][99] such as massprepared sulfides or sulfur oxides, the molten salt method allows some reactions that usually must be carried out in an inert gas to be carried out in air, with reduced costs and effective control over the morphology and size of the crystals.…”
Section: Molten Salt Methodsmentioning
confidence: 99%